MO053INHIBITION OF SODIUM PHOSPHATE TRANSPORTER NPT2A IMPROVES EXPERIMENTAL VASCULAR CALCIFICATION AND PHOSPHATE HOMEOSTASIS IN RATS. (6th June 2020) - Klar, Juergen; Anja, Giese; Ehrmann, Alexander; Thiel, Christoph; Riedl, Bernd; Eitner, Frank
Abstract: Background and Aims: A dysregulated phosphate homeostasis is strongly associated with mortality, cardiovascular events and vascular calcification, particularly in patients suffering from CKD. Inhibition of the tubular phosphate transporter Npt2a provides a novel and unique mechanism to address phosphate homeostasis imbalance and vascular calcification. Method: Npt2a activity was measured in a cell-based assay, using a stable CHO cell line with inducible Npt2a expression. Male Wistar rats were used for all experiments. Healthy rats were treated orally with BAY 767, a potent Npt2a inhibitor developed at Bayer AG to assess urinary phosphate excretion. Vascular calcification was induced by administration of a pan-FGFR inh. (25mg/kg) for 10 days. Calcium content in the aorta was measured as surrogate for vascular calcification. Blood samples were withdrawn at the end of the study to determine the plasma levels of FGF-23, parathyroid hormone and phosphate with commercially available assay systems according to the manufactures protocols (FGF-23 and PTH: ELISA Kit, Immuntopics; phosphate: Pentra400 system). Results: BAY 767 was identified as potent Npt2a inhibitor, with an IC50 of 2.9/6 nM on rat/ human Npt2a, respectively, selective over Npt2b, Npt2c and Pit-1. Single dose treatments of healthy rats resulted in a significant, dose-dependent increase in urinary phosphate excretion within 16h. In an experimental vascular calcification model, massive vascular calcification and hyperphosphatemia was induced by daily oral administration of a FGFR inh. Simultaneous treatment with the Npt2a inhibitor BAY 767 significantly inhibited vascular calcification in comparison to untreated rats. In this set-up the plasma phosphate level was increased after 10 days up to 3.7 mmol/L in the FGFR inh. treated group compared to 1.9 mmol/L in control animals, whilst treatment with BAY 767 reduced plasma levels to 2.7 mmol/L. In addition, FGF-23 and PTH were also reduced under compound BAY 767 treatment. However, in the same model 2.2% lanthanum carbonate was not beneficial with respect to vascular calcification. Conclusion: Our results show for the first time that treatment with a Npt2a inhibitor improves vascular calcification by addressing urinary phosphate excretion and phosphate homeostasis in rats. Npt2a inhibition may provide a new therapeutic principle for patients suffering from disbalanced phosphate homeostasis and vascular calcifications, including CKD patients.